EMOTIONAL FACTOR OF STUDENT LEARNING: CONTENT, STRUCTURE AND SIGNIFICANCE IN SECURITY QUALITIES OF EDUCATION - Yu.O. Saunova (Academy of Cognitive and Natural Sciences, 2009)
The article deals with the problem of the emotional factor of instruction structure and essence. Author defines the notion emotional factor of instruction establishes the significance of emotional factors at the guaranteeing quality of the modern education.